Adverse functional remodelling of the subpulmonary left ventricle in patients with a systemic right ventricle is associated with clinical outcome. (31st May 2021) - Santens, Béatrice; Helsen, Frederik; Van De Bruaene, Alexander; De Meester, Pieter; Budts, Anne-Laure; Troost, Els; Moons, Philip; Claus, Piet; Rega, Filip; Bogaert, Jan; Budts, Werner
Abstract: Aims: Early recognition of adverse remodelling is important since outcome is unfavorable once patients with a systemic right ventricle (sRV) become symptomatic. We aimed assessing prognostic markers linked to short-term clinical evolution in this population. Methods and results: Thirty-three patients (76% male) with sRV (atrial switch repair for D-transposition of the great arteries and congenitally corrected transposition of the great arteries) underwent detailed phenotyping including exercise cardiac magnetic resonance and were followed over mean follow-up time of 3 years. Mean age was 40 ± 8 (range 26–57) years at latest follow-up. Adverse outcome was a composite of heart failure (HF) and tachyarrhythmia. Descriptive statistics and univariate cox regression analyses were performed. When compared with baseline: (i) most patients remained in New York Heart Association functional class I (76%), (ii) the degree of severity of the systemic atrioventricular valve regurgitation rose, and (iii) more electrical instability was documented at latest follow-up. Six (18%) of a total of 9 events were counted as first cardiovascular events (9% HF and 9% arrhythmia). NT-proBNP, oxygen pulse, left ventricle end-diastolic volume index (LVEDVi), and stroke volume index (SVi) of the subpulmonary left ventricle (LV) both in rest and at peak exercise were significantly associated with the first cardiovascular event. Conclusion: NT-proBNP was by far the best prognostic marker for clinical outcome. Adverse remodelling with increase of LVEDVi and SVi of the subpulmonary LV at rest and during exercise were associated with worse clinical outcome. We theorize that remodelling of the subpulmonary ventricle might be an early sign of a failing sRV circulation.